Research Misconduct: A Comprehensive Examination of Retracted Publications in Biomedical Literature - Shimray, Somipam R. (Journal of Information and Knowledge, 2023)
The study aims to examine retracted articles in the biomedical literature and inspect the characteristics of retracted papers. The PubMed database was searched for retracted articles from 2012 to 2022. Four hundred twenty-one retracted articles were identified and used to examine retraction characteristics, publishers, the impact factor of retracted articles, and reasons for retraction. China published more than one-third of the retracted articles. Four authors wrote 16.86 per cent of the retracted papers. Springer has the highest retraction rate. The retraction rate has been increasing since 2012. Of 421, 364 (86.46 per cent) had an IF (Journal Citation Reports). Reasons for retraction include plagiarism, fake peer review, duplication of an article, concerns/issues about data/error in data, error in analyses, error in methods, notice-limited or no information lack of IRB/IACUC approval, concerns/issues about referencing/attributions, lack of approval from the third party, lack of approval from author and author withdrawn. These findings suggest a need for a strict and more deliberate role of editors, reviewers, institutions and governments to emphasize the importance of avoiding research wrongdoing. This study reflects the erroneous mistakes made by the academic community to get their work published.